Influence of in-situ SiNx mask on the quality of N-polar GaN films. (1st March 2017) - Yan, Long; Zhang, Yuantao; Xu, Heng; Li, Ling; Jiang, Junyan; Huang, Zhen; Han, Xu; Song, Junfeng; Du, Guotong
Abstract: We utilized in-situ grown SiNx insertion mask to improve the quality of N-polar GaN films on sapphire substrates by metal-organic chemical vapor deposition. The influences of deposition time and position of SiNx insertion mask were studied. Under the optimal SiNx mask growth conditions, the full width at half maximum values of (0002) and (10 1 ¯ 2) XRD rocking curves of N-polar GaN films are decreased to 88″ and 172″, respectively. Simultaneously, Raman spectroscopy measurements reveal that SiNx mask can also reduce the tensile residual stress of N-polar GaN films. In addition, the electrical and optical properties of N-polar GaN films with and without SiNx insertion mask were investigated by temperature dependent Hall and photoluminescence measurements. It is found that N-polar GaN film with SiNx insertion mask has lower background carrier concentration, higher mobility and lower nonradiative recombination rate.